Cytochrome P450 Enzymes Involved in Metoprolol Metabolism and Use of Metoprolol as a CYP2D6 Phenotyping Probe Drug - Berger, Benjamin; Bachmann, Fabio; Duthaler, Urs; Krähenbühl, Stephan; Haschke, Manuel (Frontiers in Pharmacology, 2018)
Metoprolol is used for phenotyping of cytochrome P450 (CYP) 2D6, a CYP isoform considered not to be inducible by inducers of the CYP2C, CYP2B and CYP3A families such as rifampicin. While assessing CYP2D6 activity under basal conditions and after pretreatment with rifampicin in vivo, we surprisingly observed a drop in the metoprolol/α-OH-metoprolol clearance ratio, suggesting CYP2D6 induction. To study this problem, we performed in vitro investigations using HepaRG cells and primary human hepatocytes (before and after treatment with 20 µM rifampicin), human liver microsomes and CYP3A4-overexpressing supersomes. While mRNA expression levels of CYP3A4 showed a 15 to 30-fold increase in both cell models, mRNA of CYP2D6 was not affected by rifampicin. 1’-OH-midazolam formation (reflecting CYP3A4 activity) increased by a factor of 5 to 8 in both cell models, while the formation of α-OH-metoprolol increased by a factor of 6 in HepaRG cells and of 1.4 in primary human hepatocytes. Inhibition studies using human liver microsomes showed that CYP3A4, 2B6 and 2C9 together contributed 19.0±2.6% (mean±95%CI) to O-demethylation, 4.0±0.7% to α-hydroxylation and 7.6±1.7% to N-dealkylation of metoprolol. In supersomes overexpressing CYP3A4, metoprolol was α-hydroxylated in a reaction inhibited by the CYP3A4-specific inhibitor ketoconazole, but not by the CYP2D6-specific inhibitor quinidine. We conclude that metoprolol is not exclusively metabolized by CYP2D6. CYP3A4, 2B6 and 2C9, which are inducible by rifampicin, contribute to α-hydroxylation, O-demethylation and N-dealkylation of metoprolol. This contribution is larger after CYP induction by rifampicin, but is too small to compromise the usability of metoprolol α-hydroxylation for CYP2D6 phenotyping.